A Three-Marker FISH Panel Detects More Genetic Aberrations of AR, PTEN and TMPRSS2/ERG in Castration-Resistant or Metastatic Prostate Cancers than in Primary Prostate Tumors - Qu, Xiaoyu (Public Library of Science, 2013)
TMPRSS2/ERG rearrangement, PTEN gene deletion, and androgen receptor (AR) gene amplification have been observed in various stages of human prostate cancer. We hypothesized that using these markers as a combined panel would allow better differentiation between low-risk and high-risk prostate cancer. We analyzed 110 primary prostate cancer samples, 70 metastatic tumor samples from 11 patients, and 27 xenograft tissues derived from 22 advanced prostate cancer patients using fluorescence in situ hybridization (FISH) analysis with probes targeting the TMPRSS2/ERG, PTEN, and AR gene loci. Heterogeneity of the aberrations detected was evaluated. Genetic patterns were also correlated with transcript levels. Among samples with complete data available, the three-marker FISH panel detected chromosomal abnormalities in 53% of primary prostate cancers and 87% of metastatic (Met) or castration-resistant (CRPC) tumors. The number of markers with abnormal FISH result had a different distribution between the two groups (P<0.001). At the patient level, Met/CRPC tumors are 4.5 times more likely to show abnormalities than primary cancer patients (P<0.05). Heterogeneity among Met/CRPC tumors is mostly inter-patient. Intra-patient heterogeneity is primarily due to differences between the primary prostate tumor and the metastases while multiple metastatic sites show consistent abnormalities. Intra-tumor variability is most prominent with the AR copy number in primary tumors. AR copy number correlated well with the AR mRNA expression (rho = 0.52, P<0.001). Especially among TMPRSS2:ERG fusion-positive CRPC tumors, AR mRNA and ERG mRNA levels are strongly correlated (rho = 0.64, P<0.001). Overall, the three-marker FISH panel may represent a useful tool for risk stratification of prostate cancer patients.